2011
DOI: 10.3758/s13414-011-0112-z
|View full text |Cite
|
Sign up to set email alerts
|

Illusory conjunctions reflect the time course of the attentional blink

Abstract: Illusory conjunctions in the time domain are binding errors for features from stimuli presented sequentially but in the same spatial position. A similar experimental paradigm is employed for the attentional blink (AB), an impairment of performance for the second of two targets when it is presented 200-500 msec after the first target. The analysis of errors along the time course of the AB allows the testing of models of illusory conjunctions. In an experiment, observers identified one (control condition) or two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 35 publications
(62 reference statements)
2
8
0
Order By: Relevance
“…Although the finding of suppression as a function of lag corresponds with findings from previous studies [43], [44], [50], all of these papers reported substantially more suppression.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Although the finding of suppression as a function of lag corresponds with findings from previous studies [43], [44], [50], all of these papers reported substantially more suppression.…”
Section: Discussionsupporting
confidence: 86%
“…Whereas both our study and that of Popple and Levi [49] employed integral dimensions of the stimuli as the relevant features (colour and shape), Vul et al [43] as well as Chun [44] used composed targets (a letter surrounded by an annulus or coloured frame). Although the study by Botella and colleagues [50] did use colour as an integrated target feature, they introduced a task-switch by varying the colour of the two targets, and possibly reduced the effectiveness of colour as a target-specific feature by also varying the colour of each distractor in the stream. It is thus not inconceivable that the latter studies introduced additional factors into the AB task that further complicated the binding and subsequent selection of targets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies of the attentional blink (e.g., Chun, 1997) have noted that such misbindings are increased under conditions that produce an attentional blink, so that the failure to report T2 is sometimes because of the report of T2 + 1 or T2 − 1 instead. Such misbindings do not account for the whole of the attentional blink effect in those studies, however (e.g., Botella, Privado, Gil-Gomez de Liano, & Suero, 2011; Vul, Nieuwenstein, & Kanwisher, 2008). Nonetheless, we carried out analyses in which report of the T2 + 1 or T2 − 1 word was counted as correct, along with report of the correct word.…”
Section: Discussionmentioning
confidence: 72%